The effect of problem-centered learning strategy on developing students' skills in geometric decoration (Journal of the College of Basic Education, 2022)
That teaching in general and teaching art education in particular has become an urgent situation and not an artistic luxury in light of the great technological and cognitive greetings that the Arab countries are witnessing through the introduction of technological techniques in the classrooms. Because “what education in general and the process of teaching and learning in particular is not immune from this Successive global changes in the world of informatics and in light of the huge scientific and technological revolution, because education and education affect the progress of human civilizations